A need to help: stories of emergent behaviour from the scene of accident. Issue 3 (7th March 2018) - Kvarnlöf, Linda
Abstract : Purpose: The purpose of this paper is to investigate how spontaneous volunteers make sense of their actions at the scene of accident. More specifically, this paper focusses on the moral aspects of this sense-making process in terms of how spontaneous volunteers justify their own and others actions at the scene of accident through moral positioning. Design/methodology/approach: This is done through a narrative analysis of volunteers' retrospective stories from the scene of accident. The empirical material consists of interviews with 12 witnesses to traffic accidents. Findings: The narrative analysis identifies two central storylines: the interviewees frame their own and others' actions through norms of how one should act, and the interviewees frame their own actions by presenting themselves as a person of a certain type, sometimes positioned against an real or imaginative "other". Originality/value: Disaster sociologists have long argued that emergent behaviours and norms are one of the phenomena distinguishing disasters from everyday emergencies. However, as this paper shows, emergent behaviours and norms are also present at everyday emergencies such as traffic accidents where spontaneous volunteers can play an important role by filling the void before the arrival of emergency services.